2016
DOI: 10.1136/oemed-2015-103118
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery atherosclerosis associated with shift work in chemical plant workers by using coronary CT angiography

Abstract: Shift work could induce CAD onset via the atherosclerotic process, and shift work employment duration was associated with an increased risk of atherosclerosis in male workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As mentioned above, inflammation plays an important role in the initiation and progression of atherosclerosis. Recent studies, which have used imaging techniques to show increased carotid intima media thickness in shift workers compared to daytime workers and have evaluated coronary artery calcium scoring to show that coronary artery disease risk increases in shift workers, have provided direct evidence for the association between shift work and atherosclerosis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, inflammation plays an important role in the initiation and progression of atherosclerosis. Recent studies, which have used imaging techniques to show increased carotid intima media thickness in shift workers compared to daytime workers and have evaluated coronary artery calcium scoring to show that coronary artery disease risk increases in shift workers, have provided direct evidence for the association between shift work and atherosclerosis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included 46 studies [10,17,23,24,37,38,40,41,43,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]62,[65][66][67][68][69][70][71][73][74][75][76][77][78][79][80][81][82][83][84][85][86]91]. The overall SMD was − 0.08 (95CI − 0.12 to − 0.03; p = 0.001) with an important heterogeneity (I 2 = 85.9%) ( Fig.…”
Section: Meta-analysis Of Hdl Cholesterol For Each Type Of Shift Workmentioning
confidence: 99%
“…These results were demonstrated in well-matched individuals who had similar baseline risk factors and were not shown to be influenced by the clinical status of the participants. To our knowledge, the only study attempting to examine the effect of shift work on CAD with the use of CCTA was recently done in 110 factory workers [15]. The results of this study showed that night shift workers suffered from a more extensive CAD burden than day shift workers.…”
Section: Discussionmentioning
confidence: 48%